Evaluation of Reference Centers for Special Immunobiologicals implementation - Laura Andrade Lagôa Nóbrega; Hillegonda Maria Dutilh Novaes; Ana Marli Christovam Sartori (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the Reference Centers for Special Immunobiologicals and evaluate their implementation considering formal regulations. METHODS We conducted a program evaluation, of evaluative research type. From August 2011 to January 2012, a questionnaire was applied to the 42 Reference Centers for Special Immunobiologicals existing in the Country, approaching the structure, human resources, and developed activities dimensions. We conducted a descriptive analysis of data and used a clustering for binary data with the squared Euclidean distance, by the farthest neighbor method, to aggregate services with similar features. RESULTS We observed great diversity among the services in the three dimensions. The clustering resulted in five service profiles, named according to their characteristics. 1) Best structure: 12 Reference Centers for Special Immunobiologicals with the highest proportion of services with the minimum of rooms recommended, purpose-built vaccine refrigerators, preventive maintenance of the cold chain, and oxygen source. 2) Immunobiologicals distributor: six Reference Centers for Special Immunobiologicals that distributed more than applied immunogens; no doctor present for more than half of the working hours and no purpose-built vaccine refrigerators . 3) Incipient implementation: five Reference Centers for Special Immunobiologicals with inadequate structure, such as absence of purpose-built vaccine refrigerators, preventive maintenance of the cold chain and oxygen source; none had computer. 4) Vaccination rooms: 13 Reference Centers for Special Immunobiologicals, everyone did routine immunization, most participated in vaccination campaigns. 5) Teaching and research: six services, all inserted into teaching hospitals, developed researches and received trainees; most had doctors in more than half of the working hours. CONCLUSIONS The evaluation of the Reference Centers for Special Immunobiologicals implementation was based on the profiles found and considered the official regulations: services categorized as "better structure" and "teaching and research" were considered implemented; "immunobiologicals distributor" and "vaccination room" services, partially implemented, and the ones with the "incipient implementation" profile, not implemented. The results of this evaluation can contribute to the reformulation of the services, considering the current context.